Pengaruh Media Buku Cerita Bergambar Terhadap Kemampuan Membaca Nyaring Siswa Kelas 2 Sekolah Dasar Islam Al-Fajri Kota Bekasi Tahun Ajaran 2022/2023 - Andien Dwi Ryzka; Nani Solihati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The research was conducted because it was suspected that there was an effect of picture storybooks on the ability to read aloud of students of Al-Fajri Islamic Elementary School, Bekasi City in the academic year 2022/2023. Quantitative research method One Group Pretest-Posttest Desig and Purposive Sampling technique chosen for the sample. Posttes minimum 71, maximum 92, average 81.68 very good category. While the standard deviation value is 5.47 which is still smaller than the average value (mean) of 81.68. This shows that the Posttest data deviation is good. The result is that storybooks with pictures show improvement in reading ability.